2022
DOI: 10.37358/mp.21.4.5549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of UAV Frame Design for Manufacturing from Thermoplastic Materials on FDM 3D Printer

Abstract: Thermoplastic materials have great usage through FDM 3D printing technology. Today, FDM 3D printer is available to the broad population, and some of the thermoplastic materials is widely used due to their small price and availability. Such thermoplastic materials are ABS (Acrylonitrile butadiene styrene) and PLA (Polylactic acid). In this paper the possibility of drone frame design optimization that can be made from ABS and PLA plastics using FDM 3D printing technology is analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Each motor is positioned at right angle to adjacent motor to ensure stability and equal weight and thrust distribution [4,5]. Three most popular materials used for drone frame are selected viz., Aluminium [6,7], Al A356 T6 [8] and ABS plastic [9,10] keeping in mind their mechanical properties like strength, rigidity (as shown in table 1), weight, cost and availability. Table 2 shows the components of drone that frame carries along with quantity and weight [11][12][13][14].…”
Section: General Design and Analysis Of Quad Copter Frame A Basic Des...mentioning
confidence: 99%
“…Each motor is positioned at right angle to adjacent motor to ensure stability and equal weight and thrust distribution [4,5]. Three most popular materials used for drone frame are selected viz., Aluminium [6,7], Al A356 T6 [8] and ABS plastic [9,10] keeping in mind their mechanical properties like strength, rigidity (as shown in table 1), weight, cost and availability. Table 2 shows the components of drone that frame carries along with quantity and weight [11][12][13][14].…”
Section: General Design and Analysis Of Quad Copter Frame A Basic Des...mentioning
confidence: 99%
“…In the design and manufacture of drones are used different materials and technologies (e.g., additive manufacturing so-called 3D printing, fused deposition modelling-FDM or fused filament fabrication-FFF, etc.). Research has shown that weight reduction is an essential parameter in the design of the frame or component parts (Palinkas et al, 2022;Piljek et al, 2022). All modern drones are equipped with a series of sensors, communication systems, localization that increase weight and reduce flight time.…”
Section: Composite Materials Used In the Structure Of Uavsmentioning
confidence: 99%
“…Three-dimensional printing currently offers a wide spectrum of applications. It is used in the construction [2,3], automotive [4,5], medical [6][7][8], decoration, machinery, dental, and textile industries. Among the most important advantages of additive technologies is the ability to produce models with complex geometry without the need for multiple manufacturing tools.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers such as acrylonitrile butadiene styrene (ABS), polylactide (PLA), and polyamide are among the best ones available [12]. ABS has been used in the electronics sector (e.g., for use in the bodies of electrical devices), sports, the automotive [4,5,13], household appliances (e.g., for use in the bodies of TV sets and radio receivers), and toys [14][15][16]. This material is characterized by its hardness and good mechanical strength, which have also been observed at low temperatures.…”
Section: Introductionmentioning
confidence: 99%